GENDER AND AGE CHARACTERISTICS OF CHILDREN HOSPITALIZED WITH CORONAVIRUS INFECTION IN UZBEKISTAN - Laziz N. Tuychiev; Umid E. Eraliev; Gulnara K. Khudaykulova; Nilufar K. Djuraeva (Central Asian Journal of Medicine, 2022)
At the beginning of the pandemic of the new coronavirus infection SARS-CoV 2, researchers drew attention to the fact that the proportion of children among those infected with COVID-19 was significantly lower than other age groups. The purpose of the study: to determine the gender and age patterns of coronavirus infection in the children’s contingent of hospitalized patients (on the example of Tashkent city). Research material and methods: The study was conducted based on the 3rd city Infectious diseases Hospital in Tashkent city during the years 2020-2021 the time periods when this medical institution was transformed into a covid hospital. Conclusion: Thus, among hospitalized children with COVID-19 (on the example of the 3rd city infectious diseases hospital in Tashkent city) during the second wave of the pandemic (I the year of 2021), an increase in the proportion of children under 1 year old was noted, due to the emergence of new strains of the virus characterized by greater involvement in the epidemic process of the children’s contingent, as well as the mitigation of quarantine restrictions and, consequently, an increased risk of infection in family clusters.